High-dose methotrexate vs. Capizzi methotrexate for the treatment of childhood T-cell acute lymphoblastic leukemia. (2018) - Jastaniah, Wasil; Elimam, Naglla; Abdalla, Khalid; AlAzmi, Aeshah A.; Aseeri, Mohammed; Felimban, Sami
Abstract: Sixty-three children (1–14 years of age) newly diagnosed with T-cell acute lymphoblastic leukemia were treated from January 2001 to December 2014. Patient outcomes were evaluated based on the regimen received; Capizzi methotrexate (C-MTX) vs. high-dose methotrexate (HDMTX). Complete remission (CR) was achieved in 54 of 60 (90.0%) patients and 3 patients died during induction. The 5-year overall survival (OS) and disease-free survival (DFS) were 88.3 ± 6.5% and 85 ± 7.5%, respectively. Post-induction, 35 patients were treated with HDMTX and 25 with C-MTX. There was no difference in OS or DFS for patients treated with HDMTX vs. C-MTX ( P > 0.05 for both). Central nervous system involvement (CNS3) was associated with inferior survival outcomes compared to Non-CNS3 patients (OS, CNS3 73.3 ± 9.1% vs.non-CNS3 93.2 ± 2.6%, (P = 0.045) and DFS, CNS3 66.7 ± 10.4% vs. non-CNS3 90.9 ± 3.1% ( P = 0.0163)). Delayed radiation in CNS3 was associated with relapse ( P = 0.0037) regardless of regimen. Thus optimization of CNS-directed therapy for patients with CNS3 is needed.